Research on Forecasting Oil and Gas Content in Individual Structures of the Absheron Peninsula Based on Satellite Data - Azizov, B.M.; Abdullayev, Kh.I.; Sultanov, J.A. (Herald of Azerbaijan Engineering Academy, 2022)
The article discusses the issues of forecasting oil and gas content in various structures of the Absheron Peninsula based on the analysis of survey materials obtained in the thermal infrared (IR) range from the Landsat 8 and NOAA-19 satellites. The peculiarity of the influence of the spectral properties of individual geological rocks on the oil and gas content was studied. It has been determined that changes in the spectral parameters of rocks make it possible to clarify issues directly related to oil and gas content, since recorded changes in rocks are considered the main factors in the formation of a pay stratum. On the basis of the results obtained, it was considered expedient to carry out geological exploration work at these sites on a regional scale.